Alfred Marshall - Taussig, F. W. (Quarterly Journal of Economics, 1924)
Journal Article Alfred Marshall Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 39, Issue 1, November 1924, Pages 1–14, https://doi.org/10.2307/1883951 Published: 01 November 1924